Peran Dukungan Sosial dalam Mengatasi Stress Akademik pada Mahasiswa: Pendekatan Penelitian Kualitatif: Penelitian - Marssel Michael Sengkey; Nova Lisye Sinaulan; Normila Syahrin; Tresensia Eka Jamali; Wulansari lisu Sarungu’; Enjelina Wisky (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Academic stress is a common phenomenon experienced by students in their higher education journey. Pressure from academic tasks, exams, and achievement demands can have a negative impact on students' mental health and academic performance. This study aims to explore the role of social support in helping students cope with academic stress through a qualitative approach. This study uses a qualitative approach with a phenomenological design. Data were collected through in-depth interviews with 7 students from various faculties who experienced high academic stress. The results showed that social support played a significant role in reducing students' academic stress levels through four main dimensions: emotional support, informational support, instrumental support, and appraisal support. Social support was shown to be an effective protective factor in coping with students' academic stress, with family and peers as the main sources of support.